Deer on airports: an accident waiting to happen - Wright, Sandra E.; Dolbeer, Richard A. (Proceedings of the Vertebrate Pest Conference, 1998)
The authors analyzed data on civil aircraft strikes with wild ungulates (deer [Odocoileus spp.], elk [Cervus canadensis] and moose [Alces alces]) in the U.S. from the Federal Aviation Administration Wildlife Strike Database and the National Transportation Safety Board Aviation Accident Database for 1983 to 1997. Prior to 1991, the FAA Form 5200-7 for reporting strikes was designated solely for bird strike data, thus, strike reports for non-avian species prior to 1991 are underrepresented. A total of 343 ungulate strikes was reported, 48 from 1983 to 1990 and 295 from 1991 to 1997. Forty-four states reported ungulate strikes with 77% of the reports from states east of the Mississippi River. November had more (P < 0.01) strikes (23%) than any other month. The strike rate (number/hr) was four to nine times greater (P < 0.01) at dusk than at night or dawn. Almost two-thirds of strikes (P < 0.01) occurred during landing, making landing at dusk in November the most likely time for deer strikes. About 79% of strikes had an effect on flight. Aircraft were damaged in 83% of strikes. Only 14% of reports indicating damage provided estimates of cost of repairs. The mean cost for these reports was $74,537. Reported human injuries have been few, but the potential exists for a major disaster. Aircraft with capacity of 101 to 380 passengers were involved in 45 (14%) of the reported strikes. Airports should adopt a "zero tolerance" for deer within the operations area. Deer removal by professional shooters, in conjunction with permanent exclusion with 3 m-high fencing, is the preferred management action.